THE EFFECT OF SOCIAL SUPPORT AND SPIRITUAL INTELLIGENCE ON THE NURSES ANXIETY LEVEL OF “IS” HOSPITAL PEKANBARU DURING COVID-19 PANDEMIC - Satria Pamungkas, Anov; Hidayah, Nurul; Urbayatun, Siti (Jurnal Ipteks Terapan, 2020)
COVID 19th pandemic situation adversely affect every aspect of life, not excluding the nursing profession who are at the forefront of dealing with patients affected by COVID-19. This causes nurses to experience stress, depression and anxiety due to increased work demands. This study aims to determine the effect of social support and spiritual intelligence on the anxiety level of nurses in the hospital. The subjects in this study were 87 nurses at the “IS” Hospital Pekanbaru. The sampling technique used in this study was purposive sampling technique. The instruments used were the COVID-19 Intelligence scale, the Social Support scale, and the Spiritual Intelligence scale. The data analysis technique used is multiple linear regression analysis. The results of the data analysis showed that F = 10.531 with a value of p = 0.000 (p <0.01) indicated that there was a very significant influence between social support and spiritual intelligence on nurses' intelligence. The results of further analysis with a partial value = -0.254. p = 0.018 (p <0.05) indicates a significant negative effect between social support and anxiety. The results of further analysis with a partial value = -0.215. p = 0.047 (p <0.05) indicates a significant negative effect between spiritual intelligence and anxiety. Based on these results, it can be concluded that there is a very significant negative effect of social support and spiritual intelligence on nurse anxiety. This means that the higher the social support and spiritual intelligence that is owned, the level of anxiety will be lower and behave harshly